Successful treatment of peritoneal recurrence after gastric cancer surgery with intravenous and intraperitoneal paclitaxel combined with S-1 chemotherapy: a case report - Kozo Miyatani; Wataru Miyauchi; Yusuke Kono; Yuji Shishido; Joji Watanabe; Takehiko Hanaki; Kyoichi Kihara; Tomoyuki Matsunaga; Manabu Yamamoto; Yoji Fukumoto; Naruo Tokuyasu; Shuichi Takano; et al. (Surgical Case Reports)
Abstract Background Despite recent advances in systemic chemotherapy, the prognosis of patients with peritoneal metastases from gastric cancer still remains poor. Nonetheless, several efficacious intraperitoneal chemotherapy regimens have recently been developed for patients with peritoneal metastases. However, no study has investigated the effectiveness of intraperitoneal chemotherapy for metachronous peritoneal metastases from gastric cancer after curative surgery. Case presentation We herein report a case of a 65-year-old man who had metachronous peritoneal metastases from gastric cancer after curative total gastrectomy who had been successfully treated with intraperitoneal chemotherapy. One month after surgery, adjuvant chemotherapy with S-1 was initiated given a final pathological stage of IIIB (pT4aN2M0). However, during adjuvant chemotherapy 12 months after surgery, tumor marker levels, which had been within normal range before surgery, increased with abdominal contrast-enhanced computed tomography (CT) revealing pelvic ascites. Thereafter, staging laparoscopy was performed, and the patient was diagnosed with peritoneal recurrence of gastric cancer. Following staging laparoscopy, an intraperitoneal access port was subcutaneously implanted for subsequent intraperitoneal chemotherapy. Combined chemotherapy with intraperitoneal and intravenous administration of paclitaxel and oral S-1 was then provided. After one course of combined chemotherapy, peritoneal lavage cytology was negative for malignancy. CT showed gradually decreasing ascites, whereas tumor marker levels returned to normal. The patient continued chemotherapy without major side effects and remained progression-free for 33 months with 36 chemotherapy cycles. Conclusions A combination regimen including intraperitoneal chemotherapy could be a promising option for patients with peritoneal recurrence after gastric cancer surgery.